Bio inspired synthesis of monodispersed silver nano particles using Sapindus emarginatus pericarp extract – Study of antibacterial efficacy - Swarnavalli, G.C.J.; Dinakaran, S.; Raman, N.; Jegadeesh, R.; Pereira, C. (Elsevier, 2017)
The synthesis of silver nanoparticles employing aqueous extract obtained from the dried pericarp of “Sapindus emarginatus” is reported. Transmission electron microscopy divulges that the silver nanoparticles are not agglomerated and are moderately mono dispersed. Size of the particle ranges from 5 to 20 nm with an average particle size of 10 nm. Ultraviolet–visible spectra recorded show typical surface plasmon resonance (SPR) at 400 nm. X-ray diffraction analysis reveals the crystalline nature of the synthesized silver nanoparticles with face-centred cubic (FCC) geometry. Silver nanoparticles thus obtained demonstrated remarkable antibacterial activity against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Proteus mirabilis, Proteus vulgaris, Klebsiella pneumonia, Pseudomonas aeruginosa and Vibrio cholerae. Freshly prepared samples and sample containing 6 nm silver nanoparticles in particular exhibited enhanced activity against gram positive bacteria. The minimal inhibitory concentration was found to be in the range of 150–250 μg/mL.